HPB P52 Presentation of acalculous cholecystitis - Are patients with acalculous cholecystitis critically unwell?. (7th December 2022) - Suresan, Srutti; Shaukat, Mubasher; Ahmad, Reddin; BinSahl, Abdullah; Naeem, Hamza; Peter, Mark
Abstract: Background: Acalculous cholecystitis (AC) is considered a life threatening inflammatory disorder of the gallbladder and is associated with high mortality and morbidity. Although it has been classically reported in critically ill patients with sepsis, trauma, burns and major surgery, AC has also been described in outpatient settings. This study aims to review the clinical presentation of AC in a busy district general hospital. Methods: Consecutive patients diagnosed with cholecystitis between March 2018 and March 2020 were identified from electronic medical database. Patients with no clinical/radiological signs of cholecystitis and confirmed gallstones on imaging were excluded. Data related to presenting symptoms, National Early Warning Score (NEWS), intensive care admission and AC related complications were retrospectively collected and analysed. Results: In this two-year study period, 61 patients were diagnosed with AC. Only 4 patients were seen in an outpatient setting. The primary presenting complaint for all patients was abdominal pain. Initial clinical presentation had a range of severity. Thirty-seven patients had NEWS of 0–1, 20 patients with NEWS 2–4 and 4 patients had NEWS >4. One patient required intensive care and another was transferred to a tertiary unit. A total of 7 patients developed complications of AC; 4 gallbladder perforations, 2 emphysematous cholecystitis and 1 gangrenous cholecystitis. There was one mortality. Conclusions: The study shows that majority of patients with AC were not critically ill. Having observed complications of AC in 11.7% of patients, this study highlights the need to have a high index of suspicion for AC in patients without coexisting critical illnesses as well.